Moral Agency Between the Times: Shared Finitude, Fragility, and Fragmentation - Heyer, Kristin E. (Theological studies, 2026)
Given how moral subjectivity and action are constituted within networks of interpersonal and social relations as they negotiate emerging questions and insights, this moral note addresses (a) enduring, individualistic signs of the times in cultural, ecclesial, and methodological contexts; (b) models of agency that center our social and finite dimensions; and (c) what such contexts and scholarship suggest for an agenda for moral agency today. It proposes that deeper attention to the function of internalized structures, the graces of failure and disorientation, and responses to ambiguity are warranted to meet the moment, between the times.